Development of an elastomeric resin for digital light processing printing - Drury, Ryan (2022)
Soft pneumatic actuators are ideal for soft robotic applications due to their innate compliance and high power-weight ratios, but their design is limited by the lack of suitable stretchable materials. In this study, a new highly elastic resin for digital light projection 3D printers, designated ElastAMBER, is prepared from a di-functional polyether urethane acrylate oligomer, and a blend of two different diluent monomers. ElastAMBER exhibits a viscosity of 1000 mPa s at 40 ºC, outperforming previously synthesized elastic resins and allowing easy printing at near room temperatures. The 3D-printed components present an elastomeric behavior with a maximum extension ratio (λ) of 4.02 ± 0.06, ultimate tensile strength of 1.23 ± 0.09 MPa, low hysteresis, and negligible viscoelastic relaxation. Its application in linear soft pneumatic actuators has been demonstrated using a bellows-like construction. ElastAMBER shows promise for creating intrinsically capacitive sensing actuators, displaying a strong correlation between actuator displacement and capacitance. The developed 3D printable ElastAMBER can find potential applications in sensors and actuators for many soft robotic and human-machine interface applications.